2018
DOI: 10.20885/ejem.vol10.iss2.art5
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic effect and risk-taking behavior in a dual banking system

Abstract: This study aims to analyze the relationship between macroeconomic factors and risk-taking behavior in a dual banking system. Adopting a panel cointegration approach, this research posits macroeconomic factors as exogenous variables and risk-taking behavior as endogenous variables. With having 468 quarterlyobservations consisting of 18 banks in Indonesia during 2010-Q4 to 2017-Q1, it finds that the risk-taking behavior of the banks has a long-term relationship with macroeconomic factors. Moreover, conventional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…It indicates that if the z-score of Islamic bank is higher, Islamic bank will have less exposure to interest rate risk. This evidence may be caused by internal resilience of Islamic bank due to a good governance in risk management including its mitigation (Fakhrunnas et al, 2018). In terms of exchange rate risk, NPF has positive and significance relationship while Z-Score has negative and significance relationship.…”
Section: Results and Analysismentioning
confidence: 96%
See 2 more Smart Citations
“…It indicates that if the z-score of Islamic bank is higher, Islamic bank will have less exposure to interest rate risk. This evidence may be caused by internal resilience of Islamic bank due to a good governance in risk management including its mitigation (Fakhrunnas et al, 2018). In terms of exchange rate risk, NPF has positive and significance relationship while Z-Score has negative and significance relationship.…”
Section: Results and Analysismentioning
confidence: 96%
“…This thought stresses that a big bank will manage risk exposure in the right manner. It is also supported by Fakhrunnas, Dari, & Mifrahi (2018) who state that Islamic bank size will mitigate the risk from unstable macroeconomic situation. It is exhibited by the ability of Islamic bank to manage risk-taking behavior comprising of credit and bankruptcy risk.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The model used was, therefore, limited to bank-specific characteristics and thus tended to exclude other external factors that may be financial and macroeconomic in nature. For example, Fakhrunnas, Dari, and Mifrahi (2018) found that risk-taking behavior by banks was related in the long-term to macroeconomic factors. It suggests that policymakers may recommend banks to merge to help the banks become more stable when in case there will be problems come from macroeconomic factors.…”
Section: Discussionmentioning
confidence: 99%
“…That is way, lenders or investors will feel more secure when investing their funds through the venture capital sharia platform. For risk of sharia principle, the risk-taking behavior of the SMEs has a long-term relationship with macroeconomic factors, so the Sharia principle is so secure from risk of inflation and interest rate (Faaza Fakhrunnas, 2018).…”
Section: Pillars Sharia Principlesmentioning
confidence: 99%